Melbourne - Cunningham, Sophie (Série cidades., 2011)
Sophie Cunningham writes a year in the city's life, a year that takes us from the heatwave that culminated on Black Saturday when temperatures soared to 47 degrees to the destructive deluge of a hailstorm. She walks through Melbournes oldest suburb to its largest market, she goes to the footy and to the comedy festival, she talks publishing and learns how to use a letterpress. Along the way she journeys deep into her own recollections of the city she grew up in, and tells stories from its history: the theft of Picasso's Weeping Woman, the Hoddle Street massacre, William Barak's trek from Healesville, the Westgate Bridge Disaster, the high drama of the 1970 and 2009 AFL grand finals and the Market Murders of the sixties. She strolls by Melbourne's rivers and creeks while considering the history of the wetlands and river that sit at Melbourne's heart. She clambers through the drains that lie beneath. For it is water the corralling of it, the excess of it, the squandering of it, the lack of it that defines Melbourne's history, its present and its future.